Redefining proton affinity for heteronuclear molecular species: quantum chemical insights - E. E. Etim; J. P. Shinggu; H. S. Samuel; B. Bako; D. K. Sahoo; L. Mweene; S. Kaya (Discover Chemistry)
Abstract One of the main problems with experimental methods for detecting proton affinity (PA) is that they cannot perform site-specific protonation. For heteronuclear molecular species that have two or more protonation sites, the experimental PA measurement only yields a single PA value for each molecular species, with no information on the protonation site. Using various quantum chemical calculation techniques, various heteronuclear molecular species with two to four protonation sites (with known experimental proton affinity values) were subjected to site-specific protonation in order to characterize the trends of the PA corresponding to the experimentally measured PA values for each heteronuclear molecular species. The results showed additional trends that correspond to the measured PA values, going beyond the widely held belief that the proton moves to the place of the highest electron density during protonation. These tendencies included the proton moving to the site of the lowest electron density. Redefining proton affinity for heteronuclear molecular species is strongly suggested by the many patterns that have been seen. Besides these tendencies, we also found some molecular species that showed significant differences between the actual and computed PA values using various approaches, suggesting that the stated experimental values might be inaccurate. These observations are explained and presented.